Electron Beam-Initiated Grafting of Methyl Methacrylate on Silicon Nanowires: Investigating Optical and Structural Properties - Muhammad Abdullah Izat Bin Mohd Yassin; Khaidzir Hamzah; Sib Krishna Ghoshal (Advances in Materials Science and Engineering)
Silicon nanowire (SiNW) is a one-dimensional nanostructured material that had been widely studied due to its potential applications in various fields. Combination of polymers and nanostructured materials offers great potential for enhanced material with many possible applications. The investigation focuses on how this grafting process influences the optical properties of SiNWs, aiming to uncover potential applications for these hybrid materials. This paper comprehensively presents the methodology and characterization of these SiNWs-MMA hybrid materials, exploring their potential applications. The experimental process begins with the preparation of six SiNWs using RF magnetron sputtering, involving the deposition of an Au catalyst and subsequent growth of SiNWs. The radiation-induced grafting involves exposing SiNWs to electron beams and subsequently grafting MMA onto the surface. The outcomes reveal that the grafting percentage of MMA onto SiNWs increases with higher radiation doses, leading to a polymer layer covering the SiNWs. This grafting is confirmed through Fourier-transform infrared (FTIR) spectroscopy, which shows characteristic peaks of MMA on the surface. X-ray diffraction (XRD) analysis demonstrates changes in crystallite size, microstrain, and dislocation density upon grafting, which are attributed to stress relief and the effect of polymer on SiNWs’ lattice. Field emission scanning electron microscopy (FESEM) images exhibit the increasing MMA layer on SiNWs as the grafting percentage increases. UV-visible spectroscopy shows that the introduction of MMA increases the optical band gap of SiNWs, attributed to changes in surface roughness due to the carbon from MMA. This study introduces a novel method of hybridizing SiNWs with MMA through radiation-induced grafting. The detailed characterization of the resulting SiNWs-MMA hybrid materials sheds light on their structural and optical properties. These findings hold the promise of innovative applications in various technological fields, further advancing nanotechnology.